Grabb's encyclopedia of flaps - Grabb, William C.; Strauch, Berish, 1933- (Philadelphia : Lippincott Williams and Wilkins, 2009)
V. 1. Now in its thoroughly updated Third Edition, this classic work is the most comprehensive reference ever published on surgical flaps for reconstructing defects in the head and neck. In clearly organized chapters, internationally recognized surgeons describe and illustrate every clinically proven flap option available for repairing every routine and unusual defect. Complementing the text are hundreds of clinical photographs and diagrams of anatomy, blood supply, flap design, and operative procedures. The Third Edition features new chapters by the original experts who have made landmark contributions to the recent literature. Many chapters from the previous edition have been completely revised. Wherever appropriate, the editors have added editorial comments to guide the reader in selection of flaps. The book is extensively indexed and organized by anatomic region, and chapters follow a uniform format that clearly presents all the information needed on each flap--indication.
volume 1. Head and neck volume 2. Upper extremities volume 3. Torso, pelvis, and lower extremities.
Includes bibliographical references and index.
Keywords: Flaps (Surgery); Surgical Flaps; Reconstructive Surgical Procedures